MATHEMATICAL MODELING OF REGULAR VORTICAL STRUCTURES IN THE ANGULAR STREAMLINED CONFIGURATIONS SURFACES. - Шквар, Є. (Science-based technologies, 2011)
The  effective  numerical  method  for  three-dimensional turbulent  flow  along  an  edge  of  a  streamwise  corner is elaborated.  The  hybrid  algebraically-differential  model  of turbulent  viscosity  has  been  adopted  to  the  given problem. Presented  results  have  demonstrated  reproduction  in calculations  the  governing  characteristics  of main and secondary vortical flows and can be effectively implemented in different energetic equipment and high-speed transport vehicles.